Productive and physiological responses of lactating dairy cows supplemented with phytogenic feed ingredients - Rodrigues, Rodrigo O [UNESP]; Cooke, Reinaldo F; Firmino, Franciele C [UNESP]; Moura, Mayara K. R [UNESP]; Angeli, Beatriz F [UNESP]; Ferreira, Hingryd A. O [UNESP]; Brandão, Alice P; Gex-Fabry, M; Ostrensky, A; Vasconcelos, Jose L. M [UNESP] (Oxford University Press (OUP), 2019)
This experiment compared milk production, milk composition, and physiological responses in lactating dairy cows supplemented with or without a mixture of condensed tannins, encapsulated cinnamaldehyde, curcumin, capsaicin, and piperine. Thirty-six lactating, multiparous, pregnant 3/4 Holstein × 1.4 Gir cows were maintained in a single drylot pen with ad libitum access to water and a total-mixed ration and were milked twice daily (d -7 to 84). On d 0, cows were ranked by days in milk (86 ± 3 d), milk yield (27.8 ± 1.0 kg), body weight (BW; 584 ± 10 kg), and body condition score (BCS; 3.04 ± 0.06) and assigned to receive (SUPP; n = 18) or not (CON; n = 18) 30 g/cow daily (as-fed basis) of Actifor Pro (Delacon Biotechnik GmbH; Steyregg, Austria). From d 0 to 84, SUPP cows individually received (as-fed basis) 15 g of Actifor Pro mixed with 85 g of finely ground corn through self-locking headgates before each milking of the day. Each CON cow concurrently received 85 g (as-fed basis) of finely ground corn through self-locking headgates. Throughout the experimental period (d -7 to 84), cows from both treatments were administered 500 mg of sometribove zinc at 14-d intervals and were monitored daily for morbidity, including clinical mastitis. Individual milk production was recorded daily, whereas milk samples were collected weekly for analysis of milk composition. Cow BW, BCS, and blood samples were also collected weekly. Cows receiving SUPP gained more BCS (P = 0.05) and had greater (P = 0.04) milk yield during the experiment compared with CON cows (0.22 vs. 0.07 of BCS, SEM = 0.05; 29.5 vs. 27.9 kg/d, SEM = 0.5). Milk composition did not differ (P ≥ 0.15) between SUPP and CON cows; hence, SUPP cows also had greater (P ≤ 0.02) production of fat-corrected and energy-corrected milk. Incidence of clinical mastitis did not differ (P ≥ 0.49) between SUPP and CON cows. No treatment differences were also detected (P ≥ 0.21) for serum concentrations of glucose and serum urea N. Mean serum haptoglobin concentration during the experiment was greater (P = 0.05) in CON vs. SUPP cows. Cows receiving SUPP had less (P ≤ 0.04) serum cortisol concentrations on d 21 and 42, and greater (P ≤ 0.05) serum concentrations of insulin-like growth factor-I on d 7, 35, and 63 compared with CON cows (treatment × day interactions; P ≤ 0.02). Collectively, supplementing phytogenic feed ingredients improved nutritional status and milk production of lactating 3/4 Holstein × 1/4 Gir cows.
Keywords: dairy cattle; milk production; physiology; phytogenic ingredients; supplementation